Pengaruh litter size dan bobot induk terhadap produksi susu kambing perah - Ajat Sudrajat; Anastasia Mamilisti Susiati; Ridwan Dwisaputra; Raden Febrianto Christi (University of Insan Cendekia Mandiri, 2022)
This study aims to determine the effect of litter size and mother weight on dairy goat milk production. The research method uses the survey method, data collection is carried out by purposive sampling with the criteria of Kaligesing dairy goats that have been lactation as many as 100 tail. The variables analyzed were the identity of the farmer, litter size, milk production and mother weight. Data analysis was carried out with descriptive analysis and simple correlation analysis. The results showed that the average litter size was 2.04 heads, milk production was 896 ml or 0.9 liters and the parent weight was 44.77 kg. The results of the correlation analysis showed a value of 0.662 or there was a strong relationship between the litter size and the weight of the mother to goat milk production. It can be concluded that the litter size and mother weight have a strong influence on the milk yield of dairy goats.